2006
DOI: 10.1016/j.conengprac.2005.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control for ramp metering of motorway traffic: A case study

Abstract: A real-life motorway in Belgium is studied and a comparison is made between a simulation of a morning rush hour situation without control and a simulation of a morning rush hour situation with ramp metering implemented. Two types of controllers are compared: a traditional ALINEA based controller and a model predictive control based ramp metering controller. In order to evaluate the controllers in a realistic framework, the simulations presented in this paper are based on real-life traffic measurements, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(95 citation statements)
references
References 8 publications
(6 reference statements)
0
94
0
1
Order By: Relevance
“…The many advantages that MPC offers are also relevant for traffic control. In fact, MPC has already been extended to conventional roadside-based non-IV traffic management [13], [14]. However, MPC can also be used for traffic management and control with intelligent vehicles.…”
Section: B Iv-based Mpcmentioning
confidence: 99%
“…The many advantages that MPC offers are also relevant for traffic control. In fact, MPC has already been extended to conventional roadside-based non-IV traffic management [13], [14]. However, MPC can also be used for traffic management and control with intelligent vehicles.…”
Section: B Iv-based Mpcmentioning
confidence: 99%
“…ramp metering of freeway networks in Bellemans et al (2006), variable speed limits and route guidance for freeway networks in Kotsialos et al (2002) and Hegyi et al (2005a,b), signal control for large-scale urban networks in Gartner et al (2002), Aboudolas et al (2010), and Lin et al (2011), and mixed urban and freeway networks in van den Berg et al (2007). A historical survey for industrial applications (other than traffic control) of MPC can be found in Qin and Badgwell (2003), while theoretical issues of MPC can be found in Garcia et al (1989), Camacho and Bordons (1999), and Mayne et al (2000).…”
Section: Solution Approach -An Mpc Controllermentioning
confidence: 99%
“…MPC for ramp metering and for conventional road-side based non-IV traffic management has been developed and implemented in [9,42,43]. Similar models as used for optimal control approach are considered.…”
Section: Control Application For Conventional Trafficmentioning
confidence: 99%